"A=\\begin{bmatrix}\n 1 & 0 & 0 \\\\\n 1 & 2 & -3 \\\\\n1 & 1 & -2 \\\\\n\\end{bmatrix} , B=\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}"We first determine the eigenvalues of the matrix A
"|A|=1(2(-2)-(-3)(1))-0+0=-1""A-\\lambda I=\\begin{bmatrix}\n 1-\\lambda & 0 & 0 \\\\\n 1 & 2-\\lambda & -3 \\\\\n1 & 1 & -2-\\lambda \\\\\n\\end{bmatrix}" Characteristic equation
"|A-\\lambda I|=0""(1-\\lambda)((2-\\lambda)(-2-\\lambda)-(-3)(1))-0+0=0""-(1-\\lambda)^2(1+\\lambda)=0""\\lambda_1=1, \\lambda_2=1, \\lambda_3=-1."These are eigenvalues.
Next, find the eigenvectors.
"\\lambda=1""\\begin{bmatrix}\n 1-\\lambda & 0 & 0 \\\\\n 1 & 2-\\lambda & -3 \\\\\n1 & 1 & -2-\\lambda \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 & 0 & 0 \\\\\n 1 & 1 & -3 \\\\\n1 & 1 & -3 \\\\\n\\end{bmatrix}" Perform row operations to obtain the rref of the matrix:
"\\begin{bmatrix}\n 0 & 0 & 0 \\\\\n 1 & 1 & -3 \\\\\n1 & 1 & -3 \\\\\n\\end{bmatrix} \\to \\begin{bmatrix}\n 1 & 1 & -3 \\\\\n 0 & 0 & 0 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix}" Now, solve the matrix equation
"\\begin{bmatrix}\n 1 & 1 & -3 \\\\\n 0 & 0 & 0 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix} \\begin{bmatrix}\n v_1 \\\\\n v_2 \\\\\nv_3 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 \\\\\n 0 \\\\\n0 \\\\\n\\end{bmatrix}" If we take
"v_2=t, v_3=s, then\\ v_1=3s-t." Therefore
"v=\\begin{bmatrix}\n 3s-t \\\\\n t \\\\\n3 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n -1 \\\\\n 1 \\\\\n0 \\\\\n\\end{bmatrix}t +\\begin{bmatrix}\n 3 \\\\\n 0 \\\\\n1 \\\\\n\\end{bmatrix}s"
"\\lambda=-1""\\begin{bmatrix}\n 1-\\lambda & 0 & 0 \\\\\n 1 & 2-\\lambda & -3 \\\\\n1 & 1 & -2-\\lambda \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 2 & 0 & 0 \\\\\n 1 & 3 & -3 \\\\\n1 & 1 & -1 \\\\\n\\end{bmatrix}" Perform row operations to obtain the rref of the matrix:
"\\begin{bmatrix}\n 2 & 0 & 0 \\\\\n 1 & 3 & -3 \\\\\n1 & 1 & -1 \\\\\n\\end{bmatrix} \\to \\begin{bmatrix}\n 1 & 0 & 0 \\\\\n 0 & 1 & -1 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix}" Now, solve the matrix equation
"\\begin{bmatrix}\n 1 & 0 & 0 \\\\\n 0 & 1 & -1 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix} \\begin{bmatrix}\n v_1 \\\\\n v_2 \\\\\nv_3 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 \\\\\n 0 \\\\\n0 \\\\\n\\end{bmatrix}" If we take
"v_3=t, then\\ v_1=0, v_2=t." Therefore
"v=\\begin{bmatrix}\n 0 \\\\\n t \\\\\nt \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 \\\\\n 1 \\\\\n1 \\\\\n\\end{bmatrix}t" Form the matrix P, whose i-th column is the i-th eigenvector:
"P=\\begin{bmatrix}\n -1 & 3 & 0 \\\\\n 1 & 0 & 1 \\\\\n0 & 1 & 1 \\\\\n\\end{bmatrix}"Form the diagonal matrix D, whose element at row i, column i is i-th eigenvalue:
"D=\\begin{bmatrix}\n 1 & 0 & 0 \\\\\n 0 & 1 & 0 \\\\\n0 & 0 & -1 \\\\\n\\end{bmatrix}" These matrices have the property that
"A=PDP^{-1}"
We first determine the eigenvalues of the matrix B
"|B|=-2(5(2)-(1)(1))+4(3(2)-(1)(1))-1(3(1)-(1)(5))=4""B-\\lambda I=\\begin{bmatrix}\n -2-\\lambda & -4 & -1 \\\\\n 3 & 5-\\lambda & 1 \\\\\n1 & 1 & 2-\\lambda \\\\\n\\end{bmatrix}" Characteristic equation
"|B-\\lambda I|=0""(-2-\\lambda)(5-\\lambda)(2-\\lambda)-3-4+(5-\\lambda)-(-2-\\lambda)+12(2-\\lambda)=0""-(\\lambda)^3+5(\\lambda)^2-8\\lambda+4=0""\\lambda_1=1, \\lambda_2=2, \\lambda_3=2."These are eigenvalues.
Next, find the eigenvectors.
"\\lambda=1""\\begin{bmatrix}\n -2-\\lambda & -4 & -1 \\\\\n 3 & 5-\\lambda & 1 \\\\\n1 & 1 & 2-\\lambda \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n -3 & -4 & -1 \\\\\n 3 & 4 & 1 \\\\\n1 & 1 & 1 \\\\\n\\end{bmatrix}" Perform row operations to obtain the rref of the matrix:
"\\begin{bmatrix}\n -3 & -4 & -1 \\\\\n 3 & 4 & 1 \\\\\n1 & 1 & 1 \\\\\n\\end{bmatrix} \\to \\begin{bmatrix}\n 1 & 0 & 3 \\\\\n 0 & 1 & -2 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix}" Now, solve the matrix equation
"\\begin{bmatrix}\n 1 & 0 & 3 \\\\\n 0 & 1 & -2 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix} \\begin{bmatrix}\n v_1 \\\\\n v_2 \\\\\nv_3 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 \\\\\n 0 \\\\\n0 \\\\\n\\end{bmatrix}" If we take
"v_3=t, then\\ v_1=-3t, v_2=2t." Therefore
"v=\\begin{bmatrix}\n -3t \\\\\n 2t \\\\\nt \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n -3 \\\\\n 2 \\\\\n1 \\\\\n\\end{bmatrix}t"
"\\lambda=2""\\begin{bmatrix}\n -2-\\lambda & -4 & -1 \\\\\n 3 & 5-\\lambda & 1 \\\\\n1 & 1 & 2-\\lambda \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n -4 & -4 & -1 \\\\\n 3 & 3 & 1 \\\\\n1 & 1 & 0 \\\\\n\\end{bmatrix}" Perform row operations to obtain the rref of the matrix:
"\\begin{bmatrix}\n -4 & -4 & -1 \\\\\n 3 & 3 & 1 \\\\\n1 & 1 & 0 \\\\\n\\end{bmatrix} \\to \\begin{bmatrix}\n 1 & 1 & 0 \\\\\n 0 & 0 & 1 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix}" Now, solve the matrix equation
"\\begin{bmatrix}\n 1 & 1 & 0 \\\\\n 0 & 0 & 1 \\\\\n0 & 0 & 0 \\\\\n\\end{bmatrix} \\begin{bmatrix}\n v_1 \\\\\n v_2 \\\\\nv_3 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n 0 \\\\\n 0 \\\\\n0 \\\\\n\\end{bmatrix}" If we take
"v_2=t, then\\ v_1=-t, v_3=0." Therefore
"v=\\begin{bmatrix}\n -t \\\\\n t \\\\\n0 \\\\\n\\end{bmatrix} =\\begin{bmatrix}\n -1 \\\\\n 1 \\\\\n0 \\\\\n\\end{bmatrix}t" Since the number of eigenvectors is less than dimension of the matrix, then the matrix is not diagonalizable.
The matrix B is not diagonalizable.
b) Find inverse of the matrix B in part a) of the question by using Cayley-Hamiltion theorem.
"B=\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}"
"|B|=-2(5(2)-(1)(1))+4(3(2)-(1)(1))-1(3(1)-(1)(5))=4\\mathrlap{\\,\/}{=}0"
We have
"B-\\lambda I=\\begin{bmatrix}\n -2-\\lambda & -4 & -1 \\\\\n 3 & 5-\\lambda & 1 \\\\\n1 & 1 & 2-\\lambda \\\\\n\\end{bmatrix}"
"p(\\lambda)=|B-\\lambda I|="
"=(-2-\\lambda)(5-\\lambda)(2-\\lambda)-3-4+(5-\\lambda)-(-2-\\lambda)+12(2-\\lambda)="
"=-(\\lambda)^3+5(\\lambda)^2-8\\lambda+4" Thus, we have obtained the characteristic polynomial
"p(\\lambda)=-(\\lambda)^3+5(\\lambda)^2-8\\lambda+4" of the matrix B.
The Cayley-Hamilton theorem yields that
"0=p(B)=-B^3+5B^2-8B+4I" where O is the 3×3 zero matrix.
Rearranging terms, we have
"B^3-5B^2+8B=4I""B({1 \\over 4}(B^2-5B+8I))=I" Similarly, we have
"({1 \\over 4}(B^2-5B+8I))B=I" It follows from these two equalities that the matrix
"{1 \\over 4}(B^2-5B+8I)" is the inverse matrix of B.
Therefore, we have
"B^{-1}={1 \\over 4}(B^2-5B+8I)"
"B^2=\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}="
"=\\begin{bmatrix}\n -9 & -13 & -4 \\\\\n 10 & 4 & 4 \\\\\n3 & 3 & 4 \\\\\n\\end{bmatrix}"
"B^2-5B+8I=\\begin{bmatrix}\n -9 & -13 & -4 \\\\\n 10 & 4 & 4 \\\\\n3 & 3 & 4 \\\\\n\\end{bmatrix}-5\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}+"
"+8\\begin{bmatrix}\n 1 & 0 & 0 \\\\\n 0 & 1 & 0 \\\\\n0 & 0 & 1 \\\\\n\\end{bmatrix}=\\begin{bmatrix}\n 9 & 7 & 1 \\\\\n -5 & -3 & -1 \\\\\n-2 & -2 & 2 \\\\\n\\end{bmatrix}"
Then the inverse matrix of B is
"B^{-1}=\\begin{bmatrix}\n 9\/4 & 7\/4 & 1\/4 \\\\\n -5\/4 & -3\/4 & -1\/4 \\\\\n -1\/2 & -1\/2 & 1\/2 \\\\\n\\end{bmatrix}"
c) Find the inverse of the matrix A in part a) of the question by finding its adjoint.
"B=\\begin{bmatrix}\n -2 & -4 & -1 \\\\\n 3 & 5 & 1 \\\\\n1 & 1 & 2 \\\\\n\\end{bmatrix}""|B|=-2(5(2)-(1)(1))+4(3(2)-(1)(1))-1(3(1)-(1)(5))=4\\mathrlap{\\,\/}{=}0"
"C_{11}=\\begin{vmatrix}\n 5 & 1 \\\\\n 1 & 2\n\\end{vmatrix}=9, C_{12}=-\\begin{vmatrix}\n 3 & 1 \\\\\n 1 & 2\n\\end{vmatrix}=-5, C_{13}=\\begin{vmatrix}\n 3 & 5 \\\\\n 1 & 1\n\\end{vmatrix}=-2,"
"C_{21}=-\\begin{vmatrix}\n -4 & -1 \\\\\n 1 & 2\n\\end{vmatrix}=7, C_{22}=\\begin{vmatrix}\n -2 & -1 \\\\\n 1 & 2\n\\end{vmatrix}=-3, C_{23}=-\\begin{vmatrix}\n -2 & -4 \\\\\n 1 & 1\n\\end{vmatrix}=-2,"
"C_{31}=\\begin{vmatrix}\n -4 & -1 \\\\\n 5 & 1\n\\end{vmatrix}=1, C_{32}=-\\begin{vmatrix}\n -2 & -1 \\\\\n 3 & 1\n\\end{vmatrix}=-1, C_{33}=\\begin{vmatrix}\n -2 & -4 \\\\\n 3 & 5\n\\end{vmatrix}=2."
"Adj(B)=C^T=\\begin{bmatrix}\n 9 & 7 & 1 \\\\\n -5 & -3 & -1 \\\\\n-2 & -2 & 2 \\\\\n\\end{bmatrix}"
"B^{-1}={1 \\over {|B|}}C^T=\\begin{bmatrix}\n 9\/4 & 7\/4 & 1\/4 \\\\\n -5\/4 & -3\/4 & -1\/4 \\\\\n -1\/2 & -1\/2 & 1\/2 \\\\\n\\end{bmatrix}"
"B^{-1}=\\begin{bmatrix}\n 9\/4 & 7\/4 & 1\/4 \\\\\n -5\/4 & -3\/4 & -1\/4 \\\\\n -1\/2 & -1\/2 & 1\/2 \\\\\n\\end{bmatrix}"
Comments
Leave a comment